Implementation of the Competency-Based Curriculum Development Model at MTs Plus Al-Azhar Wlingi Blitar - Zuyyina Ilmy Azizah; Muhamad Odi Tondi Naustion; Miftah Hur Rahman Zh; Slamet Daroini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The rapid advancement of technology, the Industrial Revolution 4.0, and ongoing social changes demand that education become more responsive and adaptive to contemporary challenges. In this context, the implementation of the Competency-Based Curriculum (CBC) in madrasas is essential for developing students' practical skills that are relevant to workforce demands and global challenges. This study aims to analyze the implementation of CBC at MTs Plus Al-Azhar Wlingi Blitar, evaluate its impact on students' competency development, and identify the challenges faced in its implementation. The research employs a qualitative approach with in-depth interviews conducted with the principal, teachers, and administrative staff directly involved in the CBC implementation. Based on interviews with the principal, curriculum vice principal, and teachers, the findings indicate that although there have been successes in CBC implementation, significant challenges remain. These include mastering more varied teaching techniques, time and resource constraints in project-based learning, and a gap between the skills taught and the needs of the industrial world. Proposed solutions include enhancing professional training for teachers, optimizing project-based learning planning, improving technological infrastructure, and strengthening partnerships with the industrial sector through activities such as field studies.